Effect of Burnout on Post-traumatic Stress Disorder Symptoms Among Firefighters in Korea: Data From the Firefighter Research on Enhancement of Safety & Health (FRESH) - Woojin Kim; Munjoo Bae; Sei-Jin Chang; Jin-Ha Yoon; Da Yee Jeong; Dae-Sung Hyun; Hye-Yoon Ryu; Ki-Soo Park; Mi-Ji Kim; Changsoo Kim
Objectives It is well-known that post-traumatic stress disorder (PTSD) among firefighters contributes to their job-related stress. However, the relationship between burnout and PTSD in firefighters has rarely been studied. This study therefore explored the association between burnout and its related factors, such as trauma and violence, and PTSD symptoms among firefighters in Korea. Methods A total of 535 firefighters participated in the Firefighter Research on Enhancement of Safety & Health study at 3 university hospitals from 2016 to 2017. The 535 participants received a baseline health examination, including questionnaires assessing their mental health. A Web-based survey was also conducted to collect data on job-related stress, history of exposure to violence, burnout, and trauma experience. The associations among burnout, its related factors, and PTSD symptoms were investigated using structural equation modeling. Results Job demands (β=0.411, p<0.001) and effort-reward balance (β=-0.290, p<0.001) were significantly related to burnout. Burnout (β=0.237, p<0.001) and violence (β=0.123, p=0.014) were significantly related to PTSD risk. Trauma (β=0.131, p=0.001) was significantly related to burnout; however, trauma was not directly associated with PTSD scores (β=0.085, p=0.081). Conclusions Our results show that burnout and psychological, sexual, and physical violence at the hands of clients directly affected participants' PTSD symptoms. Burnout mediated the relationship between trauma experience and PTSD.